MOFs nanosheets derived porous metal oxide-coated three-dimensional substrates for lithium-ion battery applications. (August 2016) - Fang, Guozhao; Zhou, Jiang; Liang, Caiwu; Pan, Anqiang; Zhang, Cheng; Tang, Yan; Tan, Xiaoping; Liu, Jun; Liang, Shuquan
Abstract: Porous nanosheet-structured materials have received great attention because of their promising applications in energy field. Construction of porous metal oxides nanosheets on three-dimensional (3D) electro-conductive substrates is an effective way to further enhance electrochemical performance of energy storage devices. Herein, porous transition metal oxides (i.e. ZnO, Co3 O4 ) nanosheets derived from MOFs coated 3D substrates (i.e. 3D nickel foam, carbon fiber) are successfully synthesized by a facile liquid-phase deposition method with subsequent calcination. The growth mechanism of MOFs with nanosheet morphology coated 3D substrates is investigated. As a proof of concept application, the Co3 O4 /3DNF hybrid, possessing the advantages of porous nanosheet-structured and 3D electro-conductive substrates, is used as a binder-free anode material for lithium-ion battery, which exhibits high-rate capability and long-term cyclic stability. High discharge capacities of 1135, 1268, 1226, 1130, 923, 751, and 543 mA h g −1 are obtained at the current densities of 0.2, 0.5, 1, 2, 5, 10, and 20 A g −1, respectively. Even measured at 25 A g −1, it still retains a desired discharge capacity of 364 mA h g −1 . Besides, the long-term cyclic stability up to 2000 cycles can be obtained at 5 A g −1 and 20 A g −1 . Graphical abstract: Porous transition metal oxides derived from MOFs nanosheets coated three-dimensional substrates (i.e. nickel foam, carbon fiber) are successfully synthesized by a facile liquid-phase deposition method with subsequent calcination. The growth mechanism of MOFs nanosheets coated 3D substrates is investigated. As a proof of concept application, the Co3 O4 /3DNF hybrid exhibits high-rate capability and long-term cyclic stability as binder-free anodes for lithium ion batteries. Highlights: We report the first synthesis of MOFs nanosheets derived porous metal oxide-coated 3D substrates. The growth mechanism of MOFs nanosheets coated 3D substrates is proposed. Co3 O4 /3DNF hybrid exhibits high-rate capability and long-term cyclic stability for lithium-ion battery applications.